Üniversite Öğrencilerinin Bilgi Kaynakları / Knowledge Sources of University Students - Acun, İsmail and Yücel, Cemil and Demirhan, Gökhan (Journal of History Culture and Art Research, 2018)
Abstract The aim of the study is to examine university students’ preferred sources of knowledge. A survey design was employed. A measurement instrument consisting of 18 items and 6 dimensions, named "authority", "social media", "religion", "science", "tradition" and "experience" was applied to 2253 university students from 12 public universities at different regions, Turkey. The data obtained were analyzed using descriptive statistics and variance tests. It is found out that the most preferred sources of knowledge for university students are "experience" and "authority, and the least preferred sources of knowledge are "religion" and "social media". In addition, it is determined that the knowledge source preferences of university students differ significantly in some sub-dimensions according to gender, grade average, socio-economic level and political views. Öz Üniversite öğrencilerinin tercih ettikleri bilgi kaynaklarını incelemeyi amaçlayan bu çalışmada, nicel betimsel tarama deseni kullanılmıştır. Bilgi kaynaklarını tespit etmek amacıyla geliştirilen 18 maddelik, “otorite”, “sosyal medya”, “din”, “bilim”, “gelenek” ve “tecrübe” olmak üzere 6 boyuttan oluşan ölçme aracı Türkiye’nin farklı bölgelerinden 12 devlet üniversitesinde öğrenim gören 2253 üniversite öğrencisine uygulanmıştır. Elde edilen veriler betimsel istatistikler ve varyans testleri kullanılarak çözümlenmiştir. Üniversite öğrencilerinin en çok tercih ettikleri bilgi kaynaklarının “tecrübe” ve “otorite” olduğu, en az tercih edilen bilgi kaynaklarının ise “din” ve “sosyal medya” olduğu tespit edilmiştir. Ayrıca, üniversite öğrencilerinin bilgi kaynağı tercihlerinin bazı alt boyutlarda cinsiyet, not ortalaması, sosyo-ekonomik seviye ve siyasi görüşlerine göre anlamlı bir şekilde farklılaştığı tespit edilmiştir.